2021
DOI: 10.3389/fmed.2021.681907
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurines in Inflammatory Bowel Disease. How to Optimize Thiopurines in the Biologic Era?

Abstract: Thiopurines have been a cornerstone in the treatment of inflammatory bowel disease (IBD). Although they have been used for more than 50 years, there are still some unsolved issues about their efficacy and, also, some safety concerns, mainly the risk of myelosuppression and life-threatening lymphoproliferative disorders. Furthermore, the development of biological therapy raises the question whether there is still a role for thiopurines in the IBD treatment algorithm. On the other hand, limited cost and wide ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 148 publications
0
15
0
Order By: Relevance
“…29,30 The aforementioned observations concerning the benefitrisk balance have also fuelled questioning on the position of thiopurines in the IBD treatment algorithm. 26,31 Interestingly, particularly in the perspective of consensus guidelines, such as the ECCO's, a recent international survey among more than 400 IBD physicians revealed that the majority of physicians still resort to thiopurines in a substantial proportion of patients and believe that thiopurines will still be an important part of the IBD treatment in the future. Moreover, 70% of respondents (strongly) agreed that thiopurines are effective as monotherapy in both CD and UC.…”
Section: Epstein-barr Virus [Ebv]; Human Papillomavirus [Hpv]mentioning
confidence: 99%
“…29,30 The aforementioned observations concerning the benefitrisk balance have also fuelled questioning on the position of thiopurines in the IBD treatment algorithm. 26,31 Interestingly, particularly in the perspective of consensus guidelines, such as the ECCO's, a recent international survey among more than 400 IBD physicians revealed that the majority of physicians still resort to thiopurines in a substantial proportion of patients and believe that thiopurines will still be an important part of the IBD treatment in the future. Moreover, 70% of respondents (strongly) agreed that thiopurines are effective as monotherapy in both CD and UC.…”
Section: Epstein-barr Virus [Ebv]; Human Papillomavirus [Hpv]mentioning
confidence: 99%
“…In addition, NUDT15 genotyping may be helpful, specifically in Asian populations. 8 Furthermore, allopurinol co-administration with low-dose thiopurines, or a switch to-or first-line use of thioguanine have also proven valuable in enhancing clinical benefit and tolerability, particularly when metabolic skewing (towards methylation) is present. 9,10 These well documented observations have led to the recent registration of 6-TG for the treatment of IBD in the Netherlands.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…By means of thiopurine methyltransferase testing and therapeutic drug monitoring, improvement of therapeutic success may be achieved. In addition, NUDT15 genotyping may be helpful, specifically in Asian populations 8 . Furthermore, allopurinol co‐administration with low‐dose thiopurines, or a switch to‐ or first‐line use of thioguanine (6‐TG) have also proven valuable in enhancing clinical benefit and tolerability, particularly when metabolic skewing (towards methylation) is present 9,10 .…”
mentioning
confidence: 99%
“…thiopurine and infliximab) might be an option. Also, monotherapy with natural products may be considered[ 60 , 80 , 81 ]. Vedolizumab (an adversary of α4β7 integrin) is significantly explicit for movement on the gut, hence it is favorable for fundamental or pneumonic responses in COVID-19[ 62 , 82 ].…”
Section: Ibd In Covid-19: Treatment Approachmentioning
confidence: 99%